Oral Health Knowledge as a Determinant of Periodontitis among the Elderly - Kurniawati, Ririn; Hadi, Sunomo; Prasetyowati, Silvia (FORIKES, 2026)
Periodontitis is a progressive inflammatory condition affecting the supporting structures of the teeth, often originating from untreated gingival inflammation and potentially leading to tooth loss. This condition represents a significant public health concern, particularly among older adults, due to its impact on oral function, quality of life, and overall health. Limited knowledge regarding oral health is considered a critical contributing factor, as it may hinder preventive behaviors and timely treatment-seeking, thereby increasing the risk of disease progression. Therefore, understanding the role of knowledge in the occurrence of periodontitis is essential. This study aimed to examine the relationship between elderly knowledge of oral health and the incidence of periodontitis. A cross-sectional design was employed, involving 48 elderly participants aged 60–80 years selected using the Slovin formula. Data were collected through questionnaires to assess knowledge and clinical observation to determine the presence of periodontitis. Statistical analysis was conducted using the Chi-square test. The results showed that the majority of respondents had low levels of oral health knowledge, and more than half of the participants experienced periodontitis. Bivariate analysis revealed a statistically significant association between knowledge and the incidence of periodontitis (p < 0.05), indicating that lower knowledge levels were correlated with a higher occurrence of the disease. This finding suggests that knowledge plays an important role in influencing oral health status among the elderly. In conclusion, knowledge is a determinant factor in the occurrence of periodontitis among older adults, where inadequate knowledge is associated with an increased risk of the disease.Keywords: periodontitis; knowledge; elderly